Duration and intensity of fluconazole for prophylaxis in preterm neonates: a meta-analysis of randomized controlled trials. Issue 1 (December 2016) - Che, Datian; Zhou, Hua; Li, Te; Wu, Bin
Abstract Background The currently available evidence shows fluconazole is an effective prophylaxis treatment against invasive fungal infections in preterm neonates in neonatal intensive care units (NICUs). However, the duration and dosing of this prophylaxis treatment remain controversial. Thus, a meta-analysis and systematic review are necessary. Methods PubMed and EMBASE were systematically searched with no restrictions. All relevant citations that compared prophylactic fluconazole and no prophylaxis were considered for inclusion. Pooled effect estimates were obtained through fixed- and random-effects meta-analyses, and a meta-regression was used to explore the sources of heterogeneity in the data. Results Five independent randomized controlled clinical trials (RCTs) involving 1006 preterm neonates were identified. Compared with no prophylaxis, the overall combined relative risks (RRs) of invasive fungal infection with the 28- and 42-day durations of prophylactic fluconazole were 0.80 (95 % CI 0.48–1.35, p  = 0.4048) and 0.30 (95 % CI 0.15–0.58, p  = 0.0004), respectively. The fluconazole dose had no significant impact on the RR of invasive fungal infections. The RR of mortality presented no significant differences between prophylactic fluconazole and no prophylaxis (RR 0.82, 95 % CI 0.60 to 1.12, p  = 0.2093). Conclusions Prophylaxis with fluconazole for 42 days was found to be superior to no prophylaxis as a strategy for preventing invasive fungal infection in preterm infants in NICUs except in terms of mortality. The dosing regimen of prophylactic fluconazole may have no impact on the outcome; however, due to the limitations of the available data, further research is needed.